2021
DOI: 10.1186/s12889-021-11342-2
|View full text |Cite
|
Sign up to set email alerts
|

Feeling about living arrangements and associated health outcomes among older adults in India: a cross-sectional study

Abstract: Introduction Advancement in the field of gerontology has been concerned with the well-being of older adults in a family setup that is associated with caregiving and support. While family life and well-being are defined by emotion, caregiving, and support activities, dissatisfaction/discontent with living arrangements is a public health concern, which is increasing with a rise in the proportion of the older population in the country. The study examines the association of dissatisfaction with liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
1
7
0
1
Order By: Relevance
“…Further, in the present study, functional difficulty is observed higher among currently unmarried respondents including widows. This supports the notion that in India where women have traditionally depended on the spouses for support, widowhood may have considerable negative impact on their socioeconomic and health status [ 41 , 66 ]. The older people from the poorest and BPL category had a higher onset of functional difficulty compared to the richest and non-BPL population.…”
Section: Discussionsupporting
confidence: 76%
“…Further, in the present study, functional difficulty is observed higher among currently unmarried respondents including widows. This supports the notion that in India where women have traditionally depended on the spouses for support, widowhood may have considerable negative impact on their socioeconomic and health status [ 41 , 66 ]. The older people from the poorest and BPL category had a higher onset of functional difficulty compared to the richest and non-BPL population.…”
Section: Discussionsupporting
confidence: 76%
“…Also, the interactive effect of marital status and living arrangement with depression was concordant with a recent study in Japan that has shown the adverse impact of both widowhood and living alone on depressive symptoms 52 . The possible explanation for the negative effect of widowhood on psychological wellbeing may be the increased stress due to spousal loss that results in reduced emotional support and lack of financial support 53,54 . Also, as documented, solo-living older individuals are less likely to have a family or close friends to talk to and are thus more likely to have a strong sense of loneliness resulting in depression [55][56][57] .…”
Section: Discussionmentioning
confidence: 99%
“…In Indian context, family is an institution which lays the seeds of social cohesion and provides social security and economic support to the older population. Also, residing with family is most preferred and satisfactory living arrangement among older people in India which is associated with improved psychological wellbeing [ 23 25 ]. A recent study in India found that older adults who lived alone and were widowed had higher chances of depression [ 26 ].…”
Section: Introductionmentioning
confidence: 99%